A Place for Zero in the Brain. Issue 8 (August 2016) - Rinaldi, Luca; Girelli, Luisa
Abstract : It has long been thought that the primary cognitive and neural systems responsible for processing numerosities are not predisposed to encode empty sets (i.e., numerosity zero). A new study challenges this view by demonstrating that zero is translated into an abstract quantity along the numerical continuum by the primate parietofrontal magnitude system.